E-Banking, Kualitas Layanan dan Kepercayaan terhadap Kepuasan Nasabah Tabungan ( Studi pada Nasabah Bank Sinarmas KCP Sultan Agung Semarang) - Wahyu Nugroho; Euis Soliha (Jurnal Bisnis dan Ekonomi, 2018)
This study aims to examine and analyze the effect of E-Banking, Quality of service, and belief on customer satisfaction. Analyzer used multiple regression, as for to test hypothesis using t test. Data collection through questionnaires with measurements using Likert scale 5 (five) alternative answers. The object of research is the customer of Bank Sinarmas Kcp Sultan Agung Semarang. The number of samples in this study is 100 respondents. Sampling technique using total sample. The result of the research shows that (1) E-Banking has positive and significant effect on customer satisfaction (2) Quality of service has no effect and not significant to customer satisfaction, (3) Trust has positive and significant impact to customer's satisfaction.